IMPLEMENTASI PENDIDIKAN INFORMAL HINDU DALAM MENJAGA POLA KOMUNIKASI REMAJA PADA PERGAULAN SEHARI-HARI - I Ketut Sudarsana (Jurusan Ilmu Komunikasi UTM, 2018)
ABSTRACTThe development of adolescents today is very worrying, especially teenagers is the next generation for Hindus in particular and also shoots for the nation of Indonesia. In order to avoid that association does not occur among adolescents, parents must be able to control and nurture their children. Parents can provide knowledge about the teachings of Hinduism and can always maintain communication with adolescents. Adolescents are not wrong association and also to not fall into the negative direction that can harm the child with parents especially in the era of globalization as nowadays all sophisticated. In addition to teachers in schools, and the environment of residence for teenagers. Parents who play the most important role here so that teenagers are not wrong association in this day and age. Parents must also be able to provide understanding and pengertiaan about the teachings of Hinduism, but the teachings of Hinduism is not only to be understood and understood but also must be biased and practiced directly with all my heart in order to find happiness inwardly.